So in video‐mediated communication in the Expanding Circle. Issue 4 (14th March 2021) - Collet, Caroline; Diemer, Stefan; Brunner, Marie‐Louise
Abstract: The English discourse marker so can mark result, inference, connection, topic development, action prompting, and emergence of incipiency. In English as a Lingua Franca (ELF) contexts, it also marks hesitation, self‐correction, and floor‐holding. Our paper uses quantitative and qualitative discourse analytical methodology to examine so in a corpus of video‐mediated informal conversations between ELF speakers, where it is the most frequent discourse marker. The analysis demonstrates that all functions documented in first‐language English use also occur in ELF. We also document extended uses of so to prompt inference and to illustrate pragmatic competence, particularly in combination with other discourse markers such as okay .